Unbalanced variation after assembly and double-speed influence coefficient method in the threshing drum - Yu, Zhiwu; Li, Yaoming; Xu, Lizhang; Du, Xiaoxue; Ji, Kuizhou (International Journal of Agricultural and Biological Engineering, 2024)
Though the component of threshing drum is pre-balancing on the factory, the drum after assembly still has the problem of unbalanced vibration. In this study, the unbalance mechanism produced by assembly are introduced and the centroid propagation model in the series rotation system was established. The influence of the eccentricity and assembly phase on the assembly unbalance was studied. It is shown that there was a superposition effect between the initial centroid eccentricity caused by the machining error and the centroid eccentricity caused by assembly error, the unbalance amount under the in-phase assembly was larger than that of the anti-phase assembly. Moreover, the unbalance variation was experimentally investigated using in-field balancing detection on the test rig and combine harvester. The experiment results showed the excellent vibration reduction effect of in-field balancing, which showed a reduction of 83.0% and 85.8%. In order to increase the range of in-field balance detection and reduce the calculation error, the double-speed influence coefficient method was proposed. The proposed method adopted the way of first low-speed pre-balancing, and then high-speed precision balance, taking advantage of vibration information at two speeds and avoids nonlinear vibration conditions caused by high unbalanced vibration. Finally, the double-speed influence coefficient method was verified on the test rig. The vibration reduction effect of proposed method was better than the traditional method. Keywords: unbalanced variation; assenmbly; threshing drum; centroid propagation DOI: 10.25165/j.ijabe.20231606.7651 Citation: Yu Z W, Li Y M, Xu L Z, Du X X, Ji K Z. Unbalance variation after assembly and double-speed influence coefficient method in the threshing drum. Int J Agric & Biol Eng, 2023; 16(6): 1–10.